Wastewater Management in the Philippines: A Call for Localized Solutions and Policy Integration - Jeff Clyde G Corpuz (Environmental Health Insights)
I read with great interest the recent study by Omohwovo on wastewater management challenges in Africa, which has strong parallels with the Philippines’ own struggles in this area. Like Africa, our country is experiencing rapid population growth and urbanization without the necessary infrastructure to support effective wastewater treatment. The Philippines is also facing poor wastewater management that has led to severe heath concerns for humans, animals, and ecosystem. Since wastewater treatment and disposal facilities are rare, domestic wastewater is discharged without treatment. This has resulted in serious public health risks and environmental damage—problems that mirror those highlighted in Africa and emphasize the urgency of meeting the United Nations’ Sustainable Development Goal 6 (SDG 6) for clean water and sanitation. This paper aims to provide guidelines for the Philippine government to consider localized solutions and policy integration to solve the issue of wastewater management in the Philippines.